Marketing Innovation Based on Social Media to Drive MSME Growth during Ramadan: A Consumer Perspective Review - Damayanti, Dhita Dhora; Wahyudi, Agus; Siregar, Nelia Fariani; Sulaeman, Moh. Muklis (PT. LITERASI SAINS NUSANTARA, 2024)
The month of Ramadan often becomes a period where consumer consumption patterns and shopping behaviors undergo significant changes. The development of technology and the widespread penetration of the internet have transformed the marketing landscape, especially during Ramadan. This study aims to provide an analytical review of marketing innovation based on social media to drive MSME growth during Ramadan, examined from the consumer perspective. The research methodology used in this study is a literature review with a qualitative approach and descriptive analysis. This research is based on data obtained from Google Scholar spanning the years 2016-2024. The study results indicate that in the continually evolving digital era, marketing innovation based on social media has become a key driver in expanding reach and enhancing the growth of Micro, Small, and Medium Enterprises (MSMEs), particularly during crucial periods such as Ramadan. The implementation of social media-based marketing strategies has opened new opportunities for MSMEs to directly interact with their potential consumers, increase awareness of the products and services they offer, and build deeper relationships with consumers. Collaboration with influencers, the use of content tailored to Ramadan themes, and understanding consumer perspectives through market research are key factors in marketing success during Ramadan. Furthermore, considering social and religious values in marketing strategies can strengthen brand image and differentiate MSMEs in the increasingly competitive market.